An Analysis of The Representation of Indonesian Cultural Identity in the Film Raya and the Last Dragon - Oktriyani, Angelina; Rullyanti, Merry; Sembiring, Lina Tri Astuty Beru (Amirul Bangun Bangsa Publishing, 2025)
This study analyzes the representation of Indonesian cultural identity in the animated film “Raya and the Last Dragon”. Through a descriptive qualitative research approach, this study aims to explore how various elements of Indonesian culture are portrayed in the film, including traditional practices, values, and symbols. The analysis is based on Stuart Hall's theory of cultural representation, which allows for an examination of how Indonesian and global audiences perceive these cultural elements in a cinematic context. The findings reveal that the film incorporates important aspects of Indonesian culture, such as the traditional weapon keris and the art of batik, which serve as symbols of heritage and identity. This research focuses the importance of cultural representation in the media and its impact on the understanding of cultural Identity in a globalized world